THE EFFECT OF COMPANY REPUTATION AND CUSTOMER EXPERIENCE ON CUSTOMER LOYAL BEHAVIOR CITYLINK INDONESIA - Henry Meytra Taufik; Mutiara Rahmadini (SEAN Institute, 2022)
The object of this research is to find out how much influence customer experience has on customer loyalty with the unit of analysis of VIP customers of Citylink Indonesia Airline. The results of the study prove the influence of customer experience on customer loyalty that customers who have a positive experience are more likely to come back for another purchase, more likely to recommend a business to a friend, and less likely to switch to a competitor. The results of this test reveal that customer experience management factors contribute very much as a strategy for competitiveness in business. The literature states that emotional experience contributes greatly to customer loyalty to a company's brand. The findings are also in line with the research results that there is a significant influence of airline image and service quality on airline customer behavioral intentions. Customer experience is related to customer loyalty, because the experience of a brand involves the subjective experience and behavior of a consumer. The experience is created by the image, trust, and additional services provided by the airline. The experience that customers have can be positive, so they will be happy to make repeat purchases of these services.